Fault lines in the Constitution : the framers, their fights, and the flaws that affect us today - Levinson, Cynthia; Levinson, Sanford, 1941- (Peachtree, 2019)
Offers an in-depth look at the U.S. Constitution and issues that have risen out of its application through history, from the electoral college and filibusters to voting eligibility and presidential succession. Explores how the Constitution has evolved over time and provides suggestions as to how it can be further improved to keep it relevant and efficient.